An in situ-forming phospholipid-based phase transition gel prolongs the duration of local anesthesia for ropivacaine with minimal toxicity. (August 2017) - Li, Hanmei; Liu, Tao; Zhu, Yuxuan; Fu, Qiang; Wu, Wanxia; Deng, Jie; Lan, Li; Shi, Sanjun
Graphical abstract: Abstract: An injectable, phospholipid-based phase transition gel (PPTG) has been developed for prolonging the release of ropivacaine (RO) for local anesthesia. PPTG was prepared by mixing phospholipids, medium-chain triglyceride and ethanol. Prior to injection, the PPTG is in a sol state with low viscosity. After subcutaneous injection, the PPTG rapidly forms a gel in situ, which acts as a drug release depot as verified by in vitro release profiles and in vivo pharmacokinetics. Administering RO-PPTG to rats led to a significantly smaller initial burst release than administering RO solution or RO base suspension. Nerve blockade in guinea pigs lasted 3-fold longer after injection of RO-PPTG than after injection of RO solution. RO-PPTG showed good biocompatibility and excellent degradability in vivo . These results suggest that this PPTG-based depot system may be useful for sustained release of local anesthetics to prolong analgesia without causing systemic toxicity. Statement of Significance: The sustained release of local anesthetics at the surgical site after a single injection is the optimal method to control post-surgical pain. In situ forming implant is an attractive alternative for the sustained release of local anesthetics. However, its practical use is highly limited by certain drawbacks including high viscosity, involved toxic organic solvents and fast drug release. To date, phospholipids-based phase transition gel (PPTG) is emerging for clinical development because of the non-toxicity, biocompatibility and ready availability of phospholipids in body. Thus, we present a novel strategy for sustained release of local anesthetics to control post-surgical pain based on PPTG, which showed a prolonged duration of nerve blockade and excellent biocompatibility.